2014
DOI: 10.1073/pnas.1411082111
|View full text |Cite
|
Sign up to set email alerts
|

Platelets guide the formation of early metastatic niches

Abstract: During metastasis, host cells are recruited to disseminated tumor cells to form specialized microenvironments ("niches") that promote metastatic progression, but the mechanisms guiding the assembly of these niches are largely unknown. Tumor cells may autonomously recruit host cells or, alternatively, host cell-to-host cell interactions may guide the formation of these prometastatic microenvironments. Here, we show that platelet-derived rather than tumor cell-derived signals are required for the rapid recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
428
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(444 citation statements)
references
References 60 publications
10
428
1
5
Order By: Relevance
“…Recently, a high prevalence of platelet-derived venous thromboembolism has been reported in patients with cancer. Alternatively, platelets recruited by tumor cells may act as catalysts for acceleration of tumor growth, angiogenesis, and metastasis 37 . When the tumor volume exceeds a certain size (> 1-2 mm 3 ), angiogenesis occurs in tumors from pre-existing blood vessels, and provides the oxygen and nutrients essential to sustain tumor growth 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a high prevalence of platelet-derived venous thromboembolism has been reported in patients with cancer. Alternatively, platelets recruited by tumor cells may act as catalysts for acceleration of tumor growth, angiogenesis, and metastasis 37 . When the tumor volume exceeds a certain size (> 1-2 mm 3 ), angiogenesis occurs in tumors from pre-existing blood vessels, and provides the oxygen and nutrients essential to sustain tumor growth 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Although not identified as NETs, platelet-granulocyte complexes with tumor cells were recently demonstrated to form early metastatic niches, crucial for later metastatic progression (28). In this context, granulocyte recruitment was initiated by secretion of CXCL5 and CXCL7 by platelets upon contact with tumor cells (28).…”
Section: Netosis As a Risk Factor For Metastasismentioning
confidence: 99%
“…The clinical observation that thrombocytosis is frequently associated with cancer was made more than 100 years ago (17,18). Recent studies indicate that platelets are integral elements of the tumor microenvironment; platelets were shown to be crucial for tumor growth (19), chemoresistance (20), and metastasis (21,22). Additionally, patients with ovarian cancer with an increased number of platelets at the time of initial diagnosis have significantly worse overall and progressionfree survival (20,23).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that platelets enhance tumor growth (19,23,26), chemoresistance (20), and metastasis (21,22). Although platelet number and function can be altered by hypoxia (27)(28)(29), the functional effects of hypoxia in the tumor microenvironment on platelets are unknown.…”
Section: Introductionmentioning
confidence: 99%